Analisis Hukum Islam terhadap Perjanjian Perkawinan Mengenai Harta Bersama di Indonesia - Muhammad Rasyid Aqsha Hsb; Fatimah Fatimah (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to examine prenuptial agreements concerning joint property from the perspective of Islamic Law. The research employs a normative legal approach, analyzing commonly used prenuptial agreement documents. The findings reveal that these agreements provide detailed arrangements regarding the division of joint assets and personal property. Prenuptial agreements play a significant role in the Indonesian marriage legal system, both in terms of positive law and Islamic legal principles. Under positive law, such agreements offer a strong legal foundation for regulating joint property and safeguarding the rights of each party involved. From the perspective of Islamic law, prenuptial agreements align with the principles of justice and the protection of individual ownership within a marital relationship.